Isolation and preliminary pathogenicity of a recent feline astrovirus strain in China - Wang, Wenjie; Zhang, Ya; Wang, Xiang; Zhu, Xu; Gong, Li; Jing, Zheng; Meng, Ting; Shen, Jiayu; Tan, Yeping; Qin, Tong; Li, Zhimin; Bi, Zhenwei (Frontiers in Veterinary Science, 2025)
Feline astroviruses (FeAstVs) have been increasingly detected in cats in recent years, yet their isolation and pathogenicity remain poorly characterized. In this study, we screened 86 feline diarrheal samples and identified FeAstV in 9.3% (8/86) of the cases, most of which were co-infected with feline parvovirus (FPV). A FeAstV strain (22SDWH1003-16) was successfully isolated in F81 cells from a single FeAstV positive sample, inducing cytopathic effects (CPEs) over 15 passages. The phylogenetic tree of ORF2 classified the isolate within Mamastrovirus 2 group 1, the most common in the inter-specific transmission within cats. Experimental inoculation of four cats revealed seroconversion in all animals, transient fecal shedding in 3/4 cats, and self-limiting diarrhea in one individual. Co-infection experiments demonstrated enhanced FeAstV replication in the presence of FPV. Our findings provide the direct evidence of FeAstV-induced diarrhea in cats and highlight the role of viral co-infections in disease severity.